The prevalence of IgG4-positive plasma cell infiltrates in inflammatory bowel disease patients without autoimmune pancreatitis - Firdevs Topal,; Elif Sarıtaş Yüksel,; Neşe Ekinci,; Mete Pekdiker,; Fulya Çakalağaoğlu,; Emrah Alper,; Belkıs Ünsal, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: IgG4-related autoimmune disease can exist in other organs even when there is no evidence of autoimmune pancreatitis. The aim of our study was to determine the prevalence of IgG4-positive plasma cells in the histopathological evaluations of colon biopsy specimens in IBD patients. Materials and Methods: The number of IgG4-positive plasma cells with strong cytoplasmic immunoreactivity was counted in each colon biopsy from inflammatory bowel disease patients who had no evidence of autoimmune pancreatitis. Five high power fields (HPFs) in the highest density plasma cell infiltration area were counted and were then averaged. An average >10 cells/HPF was considered significant for IgG4-related disease. Results: We detected IgG4-positive plasma cell staining in the colon of 21 of 119 patients (17.6%). Of these 21 patients, 5 had elevated serum IgG4 levels (>140 mg/dL). Of the total, 4.2% (5/119) had both IgG4-immunstaining and elevated IgG4 serum levels. The demographic features, disease type and activity, and response to treatment (especially to steroid treatment) were similar between the IgG4-negative and IgG4-positive groups. Conclusion: In our study, 4.2% of patients with the diagnosis of IBD had elevated IgG4 serum levels and significant IGg4 immunostaining. Together, these two parameters indicate the possible diagnosis of an IgG4-related systemic disease.